CFD simulations of shear induced migration in pressure-driven flow with non-Brownian suspensions. (February 2022) - Li, Yonghui; Fu, Jingwen; Geng, Zhongfeng; Dong, He
Highlights: Modification of Parameters in the Morris-Boulay model for 3-dimensional flow Prediction of Shear Induced Migration in concentric pipes and square channels Effect of inlet solid volume fraction, length and gap width on Non-Brownian Suspensions Abstract: Solid-liquid suspension systems exist widely in various industrial processes. Shear induced migration (SIM) is one of the important phenomena for suspension transport. With the development of model and computational effort, Computational Fluid Dynamic (CFD) methods have been adopted to predict the SIM process. The commonly used method for SIM simulation is the Morris and Boulay model, which has been commonly adopted in 2-dimensional flow. In this paper, the 3-dimensional CFD simulation of shear induced migration for non-Brownian suspensions was established. The discrepancy was found between the simulation and experimental results, indicating that modification of model parameters is required. The modified model parameters were obtained based on the comparison of simulation and experiment results. On this basis, solid volume fraction ( ϕ ) profiles of suspensions in concentric pipes and concentric square channels were explored and predicted. The influence of the inlet volume fraction ( ϕ 0 ), the ratio of half gap width to particle radius ( H / a ), and the ratio of outer wall radius to inner wall radius ( R 2 / R 1 ) were studied. For concentric pipes, asymmetric distributions between inner and outer wall of the solid volume fraction were observed. For concentric square channels, regional increase of ϕ was observed around the outer corner of the channel.